García Saraví y Juan Goytisolo: el concepto del tiempo - Bączyk-Tomaszewska, Alicja (Wydawnictwo Naukowe UAM, 2001)
The article is an attempt at a comparative analysis of texts by a contemporary Castillian writer, whose literary beginnings may be said to be rooted in the 1950s, and an Argentinean writer from La Plata, who belongs to the generation of the 1940s. What the two writers have in common is a worship of the word and similar subject matters, touching upon issues of universal character, such as life, death, the passage of time and the meaning of human existence. The thesis of the article is the following: the theme of the passage of time is the primary subject in the oeuvre of both representatives of Spanish literature. In the works of both the Argentinean and the Castillian writer there are clearly audible echoes of Gongola. Patterning themselves on Goya’s pictures, especially his “Atrocities of War”, the two use light and shadow in a similar way. Our aim was to make a comparative analysis of stylistic features of both artists and their method of creating a poetic image. Noticing the visual character of the metaphors used, we proceeded in our analysis by a method of active reading on the syntactical and phonetic planes. Subject to analysis are selected sonnets of García Saraví and some essays and novels by Juan Goytisolo.
García Saraví and Juan Goytisolo: concept of time